Development of a Multichannel Vestibular Prosthesis Prototype by Modification of a Commercially Available Cochlear Implant - Valentin, Nicolas S. (2013)
No adequate treatment exists for individuals who remain disabled by bilateral loss of vestibular (inner ear inertial) sensation despite rehabilitation. We have restored vestibular reflexes using lab-built multichannel vestibular prostheses (MVPs) in animals, but translation to clinical practice may be best accomplished by modification of a commercially available cochlear implant (CI). We developed software and circuitry to sense head rotation and drive a CI's implanted stimulator (IS) to deliver up to 1Kpulses/s via 9 electrodes implanted near vestibular nerve branches. Studies in two rhesus monkeys using the modified CI (MCI) revealed in vivo performance similar to our existing dedicated MVPs. Like commercially available CIs, our design uses an external head-worn unit (HWU) that is magnetically coupled across the scalp to the IS. The HWU must remain securely fixed to the skull to faithfully sense head motion with gyroscopes and maintain continuous stimulation. We measured normal and shear force thresholds at which HWU-IS decoupling occurred as a function of scalp thickness and calculated pressure exerted on the scalp. The HWU remained attached across the human scalp thicknesses from 3mm to 7.8mm for forces experienced during routine daily activities, with magnets exerting pressure on the scalp that remains below capillary perfusion pressure.